Peculiarities of the Legal Status of the Mayors of Lithuanian Municipalities and the Competencies (Abilities) Necessary for them in the Context of the Change of the Municipal Governance Model in 2023 - Astrauskas, Algirdas; Čelkė, Kristina (International Journal of Criminology and Sociology, 2023)
The purpose of the article is to present some of the results of a research using a questionnaire survey method conducted in February 2023, which aimed to reveal the peculiarities of the legal status and roles (dominant and others) of mayors of Lithuanian municipalities and find out what necessary competences (abilities) municipal mayors must have and in what forms they must be developed, in the presence of two different municipal governance models (the model that was applied until April 2023 and the model that is applied from April 2023). The idea to conduct such research arose just a few months before the new Local Government Law (in its revised version) entered into force in June 2022, which introduced a new municipal governance model and changed the dominant role of the mayor in the municipality. This research also took place a few weeks before the regular municipal council and mayor elections (which took place on March 5, 2023). The particular target group was chosen for this research - the mayors of Lithuanian municipalities who had served in these positions for four or more terms (referred to as "experienced" mayors during the research). No similar research (in terms of purpose and respondents) has been conducted in Lithuania. The results of the research showed that "experienced" mayors have a good understanding of the specifics of the new municipal governance model to be applied from April 2023. They are essentially prepared to take on a new dominant role (the role of municipal executive institution), replacing the previous dominant role (the role of chairman of the municipal council). The results of the research also showed that "experienced" mayors understand well what necessary competencies (abilities) municipal mayors must have, as municipal governance model and the dominant role of the municipal mayor change in it. The results of the research can be useful for improving the legal regulation of the powers of municipal institutions (municipal council and municipal mayor) and the legal framework for their relationships as well as for organizing the the improvement of the competencies of municipal mayors.